Parenting Style and Influence on Children's Education (Case Study in Lok Lahung Village, Loksado District, Hulu Sungai Selatan District) - Offeny Offeny; Diniriani Diniriani; Meina Kristiana; Yohana Yessie Natalina (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to identify parenting styles in Lok Lahung Village, analyze the influence of parental care on children, and provide a deeper understanding of the factors that influence parenting to education. The method used is descriptive qualitative involving respondents consisting of parents and children in Lok Lahung Village. The results of the study show the pattern of parenting and its influence on children's education in Lok Lahung Village. Parents in Lok Lahung Village tend to give freedom to their children to choose education according to their wishes but are always supervised by their parents.